ANALISIS PENGARUH KUALITAS PRODUK DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN CETAKAN CONTINUOUS FORM MELALUI KEPERCAYAAN MEREK (Studi pada Percetakan Jadi Jaya Group, Semarang) - Tamara Citra; Suryono Budi Santoso (JURNAL STUDI MANAJEMEN ORGANISASI, 2016)
This study aimed to analyze the effect of product quality and brand image on purchasingdecisions continuous form printing with using brand trust as mediator variable study onconsumers Jadi Jaya Group, Semarang. The quality of continuous form products is to beconsidered consumers in making a purchase at Jadi Jaya Group. The strategy used byJadi Jaya Group to maintain brand image is new innovations with printed paper-basedSecurity Printing design that makes the company different from competitors and increasebrand trust.This study used non-probability sampling is used for judgmental sampling.Data were collected from 197 respondents selected using criteria that should have madea purchase of continuous form at least twice. The method analysis used in this researchwas Maximum Likelihood test using the program of AMOS version 21.0.The results showthat the product quality and brand image has positive influence on brand trust. But,brand trust did not positive influence on purchasing decisions. Then, product quality andbrand image has positive influence on purchasing decisions continuous form at Jadi JayaGroup, Semarang.Keywords: Product Quality, Brand Image, Brand Trust, Purchasing Decisions.